Trapped in Self-Sabotage Patterns: The Role of Coping Styles in Early Adulthood with Emotionally Immature Parents - Al-aida, Alfia Najwa; Islam, Azizah Fajar (Jurnal Psikologi Terapan, 2024)
This study aims to examine the role of coping style in early adulthood with emotionally immature parents on the level of self-sabotage. The background of this research is based on the phenomenon observed in individuals who grow up with emotionally immature parents, often facing difficulties in problem-solving and engaging in self-sabotaging behaviors. This study uses a quantitative method with simple linear regression analysis to test the relationship between coping style and self-sabotage. The results show a significant relationship between the two variables, with an internalizing coping style showing a negative correlation and an externalizing coping style showing a positive correlation with self-sabotage. The effect of coping style on Self-sabotage is recorded at twenty-one percent, with the internalizing coping style having a greater impact than the externalizing coping style. This study concludes that coping style plays an important role in shaping Self-sabotage behaviors in early adulthood with emotionally immature parents. It is hoped that this research will serve as a reference for future studies and provide further insights into the relationship between coping style and Self-sabotage in individuals with emotionally immature family backgrounds.